Barron's AP English language and composition - Ehrenhaft, George; Barron's Educational Series, Inc. (Hauppauge, N.Y. : Barron's Educational Series, Inc., 2013)
Reviews subjects on the test, offers test-taking strategies and tips on essay writing, and includes five full-length practice exams with answers and explanations.
Getting acquainted with the test. Structure of the exam ; Multiple-choice questions ; Reading techniques ; Essay questions -- Diagnostic test -- Mastering multiple-choice questions. Five rules of thumb ; Language and rhetoric ; Techniques for tackling reading passages -- Mastering essay questions. Steps for writing the perfect essay ; Pointers for writing the synthesis essay ; Sample synthesis essay question ; Pointers for writing an analytical essay ; Writing a persuasive essay ; Editing and proofreading essays ; Sample analytical essays ; Answer key to mini-workouts -- Practice tests.
Includes index.
Keywords: English language -- Examinations -- Study guides; English language -- Examinations, questions, etc; English philology -- Examinations -- Study guides; English philology -- Examinations, questions, etc; English composition test -- Study guides; Advanced placement programs (Education) -- Examinations -- Study guides; Universities and colleges -- United States -- Entrance examinations -- Study guides; College entrance achievement tests -- United States -- Study guides